Peer Scaffolding Behaviors in English as a Foreign Language Writing Classroom - Chairinkam, Jittiporn; Yawiloeng, Rattana (Asian Journal of Education and Training, 2021)
This study aimed to investigate the kinds of peer scaffolding behaviors occurring during English as a Foreign Language (EFL) writing activities through three steps of writing process. The participants comprised ten English major students in writing classroom in University of Phayao selected by purposive sampling. They were classified into five expert EFL learners and five novice EFL learners according to their scores of the written paragraph they wrote before participating in the study by using writing rubric. The instruments consisted of five lesson plans through writing process and an observation form. The results analyzed by Microgenetic Analysis revealed that questioning ranked first by the total frequency of peer scaffolding all learners used, but they never applied greeting to their writing activities. However, ten learners applied various types of peer scaffolding to pre-writing activity while they hardly utilized peer scaffolding in post-writing activity. Noteworthy that both expert and novice learners were able to be scaffolders for their peers by supplementing each other’s knowledge and skills because they may be expert writers in different areas, consequently they were able to produce written works by themselves.